Meat is healthy, green and vital to social and economic sustainability: frames used by the red meat industry during development of the Nordic Nutrition Recommendations - Amanda Wood; Janice Swan; Talia Masino; Bjørk Tørnqvist; Elin Röös (Environmental Research: Food Systems)
To reduce environmental impacts from the food system, demand-side changes, especially reductions in the consumption of animal products in high-consuming populations, are needed. This will require policies promoting red meat reductions, since dietary patterns are difficult to change, but such policies will likely meet opposition from certain food industry actors. An example is provided by the Nordic Nutrition Recommendations (NNR), the evidence base underpinning all food-based dietary guidelines (FBDGs) in the Nordic countries. The updated version recommends that individuals restrict red and processed meat consumption to a maximum of 350 grams per week for health reasons, and advises ‘considerably less’ is consumed for environmental reasons. During the revision of the NNR, Nordic red meat industry actors and farmers’ associations were quick to respond to indications that lower amounts of red meat would be recommended. We conducted a frame analysis of responses relating to red meat consumption made by these actors in the public consultations on the NNR. Our analytical framework built on literature-based frames commonly used by the meat industry in countries with high meat consumption. The results showed that actors supporting the red meat industry generally opposed reductions to red meat consumption (and production) by framing red meat consumption as healthy and red meat production as providing social, economic and environmental benefits. Red meat actors also questioned the science (or scientists) supporting reductions in red meat consumption. For any national authority tasked with developing dietary recommendations, it is crucial to identify how these actors frame red meat consumption and use these frames to influence the formulation of sustainable dietary guidelines.